Multimodal Precision Imaging of Pulmonary Nanoparticle Delivery in Mice: Dynamics of Application, Spatial Distribution, and Dosimetry. Issue 49 (22nd October 2019) - Yang, Lin; Gradl, Regine; Dierolf, Martin; Möller, Winfried; Kutschke, David; Feuchtinger, Annette; Hehn, Lorenz; Donnelley, Martin; Günther, Benedikt; Achterhold, Klaus; Walch, Axel; Stoeger, Tobias; et al.
Abstract: Targeted delivery of nanomedicine/nanoparticles (NM/NPs) to the site of disease (e.g., the tumor or lung injury) is of vital importance for improved therapeutic efficacy. Multimodal imaging platforms provide powerful tools for monitoring delivery and tissue distribution of drugs and NM/NPs. This study introduces a preclinical imaging platform combining X‐ray (two modes) and fluorescence imaging (three modes) techniques for time‐resolved in vivo and spatially resolved ex vivo visualization of mouse lungs during pulmonary NP delivery. Liquid mixtures of iodine (contrast agent for X‐ray) and/or (nano)particles (X‐ray absorbing and/or fluorescent) are delivered to different regions of the lung via intratracheal instillation, nasal aspiration, and ventilator‐assisted aerosol inhalation. It is demonstrated that in vivo propagation‐based phase‐contrast X‐ray imaging elucidates the dynamic process of pulmonary NP delivery, while ex vivo fluorescence imaging (e.g., tissue‐cleared light sheet fluorescence microscopy) reveals the quantitative 3D drug/particle distribution throughout the entire lung with cellular resolution. The novel and complementary information from this imaging platform unveils the dynamics and mechanisms of pulmonary NM/NP delivery and deposition for each of the delivery routes, which provides guidance on optimizing pulmonary delivery techniques and novel‐designed NM for targeting and efficacy. Abstract : The multimodal in vivo/ex vivo imaging platform established here provides comprehensive insights into the dynamic process of pulmonary nanoparticle delivery with high temporal and quantitative 3D spatial resolution in entire mouse lungs.